Accumulation of Barium, Uranium, Cadmium and Manganese in the Sediment Core from the Pulau Cik Wan Dagang Mangrove Forests, Terengganu, Malaysia - B. Y., Kamaruzzaman; N. A. M., Shazili; Mohd Lokman,; I., Sulong (Universiti Putra Malaysia Press, 2002)
The accumulation of elements Ba, U, Cd and Mn with respect to depth was determined in a 150 cm sediment core obtained from the mangrove forests of Pulau Cik Wan Dagang, Kuala Kemaman, Terengganu, Malaysia. Generally, all elements except Mn decrease with depth and their vertical profiles show a clear boundary at about 70 cm deep. In order to assess the influence of heavy metal pollution more precisely, enrichment factors (EF) were calculated. In this study, U and Cd have EF values significantly greater than unity and may therefore be considered to be predominantly anthropogenic in origin whereas Ba and Mn which have EF values about unity are considered to be predominantly terigenous in origin.